IDENTIFYING RISK FACTORS FOR INCAUTIOUS USE OF NON-PRESCRIPTION DRUGS AMONG HIGHER EDUCATION INSTITUTIONS' STUDENTS IN EMIRATES - Al-kubaisi, Khalid Awad; Stecroix, Mark De; Vinson, Don; Abduelkarem, Abduelmula Rajab (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this research is to identify risk factors for incautious use of oral non-prescription drugs (ONPD) and inform recommendations that promote cautious ONPD use among HEI students in the UAE. Methods: A cross-sectional survey-based study was conducted with 2875 students in three randomly selected UAE universities between January and April 2014. Results: More than half (1348; 57%) of participants reported using of ONPD in the past 90 days before study commencement. Of 1348 participants reported using ONPD, one-quarter (1348; 22.2%) of ONPD was classified as incautious ONPD usage. Analgesic/antipyretic (84.9%), non-steroidal anti-inflammatory drugs (NSAIDs) (1028; 76.3%), and cough and cold drugs (562; 41.7%) were reported by the majority of participants as the most commonly used ONPD. 10 risk factors were identified for incautious ONPD use. Participants with age group of 21 years and older (OR=0.554, 95%; CI=0.373-0.823; p<0.001), female (OR=0.339, 95%; CI=0.236-0.486; p<0.001), and students from medical schools (OR=0.619, 95%; CI=0.435-0.882; p=0.008) had lower odds of being incautious users compared to lower age group, males, and students from non-medical schools. Furthermore, participants with a polypharmacy behavior had higher odds of being irresponsible ONPD user than monopharmacy users (OR=1.400, 95%; CI=1.030- 1.02; p<0.001). Conclusion: One of five students is an incautious ONPD user. There is a need for an educational and behavioral intervention to motivate students to be cautious users.